The impact of pain from medial meniscus injuries on walking movement patterns - Chen, Yiyan; Wang, Liyan; Fan, Zhiying; Zhou, Haibin; Lu, Aming (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundExisting literature provides inconclusive evidence regarding the impact of pain on movement patterns, especially in medial meniscus injuries. This study investigated how pain induced by medial meniscus injuries affects walking movement patterns, focusing on the biomechanical mechanisms. The goal was to develop targeted rehabilitation.MethodsThirty control participants (15 male, 15 female), 23 individuals with medial meniscus injury but no pain (11 male, 12 female), and 51 individuals with medial meniscus injury and pain (24 male, 27 female) were recruited. Gait data was collected using eight inertial measurement units and a video camera. Pain characteristics were assessed using the Visual Analog Scale (VAS) score, Tampa Scale for Kinesiophobia (TSK), Pain Catastrophizing Scale, and pain duration score. Statistical analyses were conducted using a one-way ANOVA to compare movement patterns among the three groups. Bivariate correlation analyses were performed within the pain group to examine the relationship between pain characteristics and movement patterns. The p was set at 0.05.Results(1) ANOVA among the groups revealed significant differences (p < 0.05) in several parameters: a shorter swing phase, reduced hip and knee angles, increased variability index, increased calf-foot mean absolute relative phase (MARP) during the support phase, and decreased calf-foot MARP during the swing phase were associated with pain. (2) Within the pain group, pain in knee extension (PKE) was negatively correlated with hip and ankle angles, stride length, and thigh-calf MARP during the support phase (p < 0.05). The VAS exhibited a negative correlation with knee angle and stride length, and a positive correlation with shock attenuation (p < 0.05). The TSK showed a positive correlation with hip and knee angles, and calf-foot MARP during the swing phase, while it was negatively correlated with stride length (p < 0.05).ConclusionMedial meniscus injury-induced pain has several adverse effects, including prolonged walking swing periods, reduced angulation, and increased variability while positively influencing coordination and shock attenuation. Pain intensity, kinesiophobia, and pain freedom contribute to these changes. Therapists should focus on pain management and movement pattern retraining to develop personalized rehabilitation. The angle of the swing phase should be emphasized during retraining.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=65961, identifier ChiCTR2000041087